Factors Associated with Treatment Compliance of Extrapulmonary Tuberculosis Patients at the End of Intensive Phase - Haque, Shah Md Ezaz ul; Khan, Azharul Islam; Islam, Md Khairul; Hossain, Md Sazzad; Hossain, Md Asif; Khan, Md Maruf Haque (Journal of Medicine, 2025)
Introduction: Tuberculosis (TB) remains a global health threat, with extrapulmonary tuberculosis (EPTB) posing particular challenges in diagnosis and treatment compliance.This study investigated factors affecting compliance among EPTB patients in Bangladesh, with a focus on those receiving treatment under the Directly Observed Treatment, Short-course (DOTS) strategy. Methodology: A cross-sectional study was conducted, collecting data from 209 individuals with EPTB using a semi-structured questionnaire at 12 DOTS centers in the Dhaka division. Patients aged 18 and older, regardless of gender, with EPTB were included. Those who were being re-treated or had serious illnesses like human immunodeficiency virus (HIV), chronic kidney disease, stroke, cancer, or cardiovascular disease (CVD) were excluded.Treatment compliance was measured by adherence to prescribed treatment, including the avoidance of missing doses, at the end of the intensive phase. Those who complied with treatment were compared with those who did not comply. Results: Of 209 respondents, the level of treatment compliance to EPTB treatment was 96% and cervical lymph node was found to be affected mostly (30%) by tuberculosis. Mean age, age group, belief about death that can result if not treated, and satisfaction from counseling by healthcare providers were significantly associated with treatment compliance (p <0.05). On binary logistic regression analysis, joint family type (AOR = 65.802; 95%CI:.58-1865.504) was independently associated with treatment compliance. Conclusion: The compliance among the extrapulmonary tuberculosis patients attending DOTS centers was 96%. The study found that mean age, age group, belief about EPTB that can result in death if not treated, satisfaction with counseling from the health care provider were associated with treatment compliance with anti-TB treatment among people with EPTB. J MEDICINE 2025; 26(2): 101-109